2011
DOI: 10.1007/s11746-011-1863-3
|View full text |Cite
|
Sign up to set email alerts
|

Cold‐Pressed Pumpkin Seed Oil Antioxidant Activity as Determined by a DC Polarographic Assay Based on Hydrogen Peroxide Scavenge

Abstract: Antioxidant (AO) activity of cold pressed pumpkin (Cucurbita pepo L.) seed oil, produced from three naked and one hulled variety, was assessed using a DC polarographic assay based on a hydrogen peroxide scavenge (HPS). Results are expressed as the decrease of the anodic oxidation current of hydrogen peroxide obtained upon addition of methanolic extract of the investigated oils. Strict correlations of HPS and (1) radical scavenging capacity against the stable free radical 1,1-diphenyl-2-picrylhydrazyl (DPPH) (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
5
15
1
Order By: Relevance
“…In the presented experiment, the content of squalene in the control sample reached 1192 mg/100 g of oil, which is a high value compared to literature data. According to Gorjanović et al (2011), squalene content in oils produced from seeds of C. pepo hulless pumpkin ranged from 549 mg/100 g of oil (cultivar BSB^-Serbia) to 788 mg/100 g of oil (cultivar BGleisdorfer Diamant^-Austria). The analysis of results obtained in our study enables concluding that squalene is a compound characterized by high lability.…”
Section: Bioactive Compound Content In Encapsulated Pumpkin Seed Oilmentioning
confidence: 99%
See 2 more Smart Citations
“…In the presented experiment, the content of squalene in the control sample reached 1192 mg/100 g of oil, which is a high value compared to literature data. According to Gorjanović et al (2011), squalene content in oils produced from seeds of C. pepo hulless pumpkin ranged from 549 mg/100 g of oil (cultivar BSB^-Serbia) to 788 mg/100 g of oil (cultivar BGleisdorfer Diamant^-Austria). The analysis of results obtained in our study enables concluding that squalene is a compound characterized by high lability.…”
Section: Bioactive Compound Content In Encapsulated Pumpkin Seed Oilmentioning
confidence: 99%
“…The stability of control pumpkin seed oil expressed as the oxidation induction time was 6.1 h. Some discrepancies occur in literature data regarding the oxidative stability of pumpkin seed oil. For example, Gorjanović et al (2011) found that the induction time of oil obtained from seeds of hulless pumpkin ranged from 4.0 h (species C. pepo, cultivar Olianka) to 4.5 h (species C. pepo, cultivar Gleisdorfer Diamant). In turn, Rezig et al (2012) reported that the oxidative stability of oil pressed from seeds of C. maxima reached 18.61 h. Noteworthy is, however, the fact that Gorjanović et al (2011) were oxidizing the sample at a temperature of 100°C, Rezig et al (2012) at a temperature of 120°C.…”
Section: Oxidative Stability Of Encapsulated Pumpkin Seed Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Pumpkin seed oil is often noted for its high antioxidant activity and oxidative stability [34,35]. Considering that the production process of pumpkin seed oil includes roasting at high temperatures, such oxidative stability is not in accordance with the general notion that higher processing temperatures decrease oxidative stability.…”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…Furthermore, Lacatusu et al () and Badea et al () reported the presence of synergistic effect of plant seed oil with UV filters that can help to reduce the usage of synthetic UV filters in the production of sunscreen products. Rabrenovic et al (), Gorjanovic et al (), and Lacatusu et al () claimed PSO contains high amount of monounsaturated fatty acids, tocopherols, and phytosterols as well as squalene, which possess high potential in medical and nutritional purposes. Besides, the polyphenols present may benefit for photoprotection and inhibition of photocarcinogen (Afaq and Katiyar, ).…”
Section: Introductionmentioning
confidence: 99%